Thesis Marking Criteria with Descriptors - Ting, Su Hie (Faculty of Education, Language and Communication, 2023)
Thesis Marking Criteria with Descriptors is a guideline for the marking of thesis and serves as a benchmark of good research reporting. This Thesis Marking Criteria with Descriptors differs from existing materials because it offers descriptors of poor, moderate and good qualities of writing and information for all key sections of a thesis. The existing materials are usually in the form of a marking sheet with listing of items and mark allocation. Other existing materials take the form of lists of desirable qualities in writing but does not operationalise the ideals to help lecturers and supervisors to judge the different standards of thesis presented to them. The Thesis Marking Criteria with Descriptors will also guide researchers and students to produce good research reports not only in the form of theses but also journal papers. The Thesis Marking Criteria with Descriptors is supported by five publications.